Argatroban dosing in obesity. Issue 163 (March 2018) - Elagizi, Stephanie; Davis, Kyle
Abstract: Purpose: Obesity is associated with significant alterations in pharmacokinetic and pharmacodynamic properties. The use of weight based anticoagulants such as argatroban may put obese patients at an increased risk of hemorrhagic events. The purpose of this study was to evaluate argatroban dosing requirements in obese vs non-obese patients. Methods: This single-center, retrospective cohort study included patients ≥18 years with suspected HIT, treated with argatroban for ≥12 h. Patients were stratified by body mass index (BMI) into obese (BMI > 30 kg/m 2 ) and non-obese (BMI ≤ 30 kg/m 2 ) groups. The primary outcome was the median maintenance dose required to achieve two consecutive therapeutic activated partial thromboplastin times. Results: A total of 121 patients were included. The median BMI in the obese vs non-obese groups was 35.8 vs 24.05 kg/m 2 (p < .0001). Although statistically significant, there was no clinically significant difference in median maintenance argatroban dose in obese versus non-obese patients (1 vs 1 μg/kg/min; p = .01). In-hospital major bleeding and in-hospital thrombosis also did not differ between the two groups. Conclusion: Obese patients require similar median argatroban maintenance doses when compared to non-obese patients. Based on these results argatroban should be dosed using actual body weight regardless of BMI. Highlights: Obesity can alter pharmacokinetic and pharmacodynamic properties of drug therapy. The use of weight argatroban may put obese patients at risk of hemorrhagic events. Argatroban dose requirements were studied in obese versus non-obese patients. Median maintenance dose was statistically but not clinically significant. In-hospital major bleeding and thrombosis did not differ between the groups.